Real-life experience with ceftobiprole in a tertiary-care hospital. (September 2020) - Durante-Mangoni, Emanuele; Andini, Roberto; Mazza, Maria Civita; Sangiovanni, Francesco; Bertolino, Lorenzo; Ursi, Maria Paola; Paradiso, Laurenza; Karruli, Arta; Esposito, Clelia; Murino, Patrizia; Corcione, Antonio; Zampino, Rosa
Highlights: Data on the use of ceftobiprole in severely ill patients, are limited. A favourable clinical outcome was observed in 20 of 29 patients receiving ceftobiprole. Three patients had ceftobiprole-related toxicity, including two cases of myoclonus. No major adverse effect on bone marrow, kidney or liver function was observed. Ceftobiprole is a safe and effective treatment for bacterial infections. Abstract: Objectives: Ceftobiprole is a new therapeutic option for bacterial pneumonia, with activity against most antimicrobial-resistant Gram-positive cocci, including methicillin-resistant Staphylococcus aureus . Data on the use of ceftobiprole in real life are limited. We evaluated the efficacy and safety of ceftobiprole in a context of a hospital practice. Methods: In a single-centre, observational, retrospective clinical study, we collected data of 29 patients undergoing ceftobiprole therapy, with a focus on clinical outcomes and adverse events. Results: There was a high burden of comorbidities in the study cohort, including kidney dysfunction (38%) and cancer (24%), and a high proportion of patients with sepsis/septic shock (72%), a central line (41%) or on mechanical ventilation (21%). Most infections were nosocomial (24, 82.8%). Ceftobiprole was mostly prescribed for pneumonia (17 patients, 58.6%), and bloodstream infections (10 patients, 34.5%), both empirically (9 cases, 31%) and as targeted therapy (20, 69%, with staphylococci as the dominant pathogens). It was the first-line drug in 15 cases (51.7%). Overall, a favourable clinical outcome was observed in the majority of cases (68.9%), with clinical cure in 3 (10.3%) and clinical improvement in 17 (58.6%). Failure of treatment occurred in seven cases (24.1%). Three patients experienced a definite ceftobiprole-related adverse event, with two cases of myoclonus. No major adverse effect on bone marrow, kidney or liver function was observed. Conclusions: Ceftobiprole, even outside current indications, may be a safe and effective treatment for resistant Gram-positive cocci infections where other drugs are inactive or poorly tolerated, and for salvage therapy.